THE ROLE OF TEACHERS AS AGENTS OF CHANGE IN SHAPING STUDENTS' CREATIVITY, CHARACTER, AND SOCIAL SENSITIVITY: A LITERATURE REVIEW - Fien Pongpalilu; Aslan Aslan (Adisam Publisher, 2025)
This research aims to examine the role of teachers as agents of change in shaping students' creativity, character and social sensitivity through a literature review. Teachers not only act as teachers, but also as facilitators, motivators, and role models who are able to create a conducive learning environment for the holistic development of student potential. Through learning innovations, integration of character values, and involving students in various social activities, teachers are expected to foster creativity, form strong character, and increase students' social sensitivity. This study uses a systematic literature review method by analysing various relevant literature sources, such as scientific journals, books and articles. The results show that the role of teachers is vital in preparing a generation that is not only intellectually smart, but also has character and cares about their social environment. Support from the school environment, collaboration with parents and the community, and the development of teacher professionalism are important factors in optimising the role of teachers as agents of change.